A history of opera : milestones and metamorphoses - Fisher, Burton D. (Opera classics library., 2005)
A comprehensive history of opera that traces each milestone in opera history from the 16th century Camerata through the next 400 years, and featurrd in depth analysis of all important genres: the Baroque, Classical, and Romantic eras, Bel Canto, Opera Buffa, German Romanticism, Wagner and music drama, Verismo, Impressionism, Expressionism, Serialism, and much more.